Endocrine-disrupting chemicals and male reproductive health - Sharma,A; Mollier,J; Brocklesby,RWK; Caves,C; Jayasena,CN; Minhas,S (Reproductive Medicine and Biology, 2020)
BackgroundA number of different types of endocrinedisrupting chemicals (EDCs) including bisphenol A, phthalates, pesticides, and other environmental chemicals have been shown to adversely impact upon male reproductive health. Understanding the potential effects of EDCs on male reproductive health may enable the development of novel treatments and early prevention of the effects of EDCs on male infertility and their potential longterm sequelae. This review critically evaluates the research performed in this area and explores potential harmful effects of EDCs in animals and humans, including the possibility of transgenerational transmission.MethodsA literature review was conducted using electronic databases using the following terms: ‘endocrine disrupt’ OR ‘endocrine disruptors’ OR ‘endocrine disruptor chemicals’ OR ‘EDC’ AND ‘sperm’ OR ‘spermatozoa’ OR ‘spermatozoon’ OR ‘male reproductive health’ OR’ male fertility’.Main findingsSeveral studies have shown that EDCs have a variety of pathophysiological effects. These include failure of spermatogenesis, embryonic development, the association with testicular cancer, and longterm metabolic effects.ConclusionsSeveral studies observe correlations between chemical doses and at least one sperm parameter; however, such correlations are sometimes inconsistent between different studies. Mechanisms through which EDCs exert their pathophysiological effects have not yet been fully elucidated in human studies.